2019
DOI: 10.3390/ijms20153833
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge of the Potential Links between Inflammation and Prostate Cancer

Abstract: Inflammation is inherent in prostatic diseases and it is now accepted that it may facilitate cellular proliferation in both benign and malignant conditions. The strong relationship between prostatic inflammation and pathogenesis of benign prostatic hyperplasia (BPH) is supported by epidemiologic, histopathologic and molecular evidence. Contrariwise, the role of inflammation in prostate carcinogenesis is still controversial, although current data indicate that the inflammatory microenvironment can regulate pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 74 publications
0
73
0
Order By: Relevance
“…Inflammation also commonly occurs in the general population with or without clinical prostatitis and in benign prostatic hyperplasia. The mechanism of how benign hyperplasia‐related inflammation differs from inflammation in prostate cancer is still unclear, but a difference was found in inflammatory cell types and proportions between the two entities 43 . Again, our study showed an inverse relationship of both chronic and acute inflammation to cancer, suggesting that the CAM‐cancer association is not driven by CAM being associated with inflammation.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Inflammation also commonly occurs in the general population with or without clinical prostatitis and in benign prostatic hyperplasia. The mechanism of how benign hyperplasia‐related inflammation differs from inflammation in prostate cancer is still unclear, but a difference was found in inflammatory cell types and proportions between the two entities 43 . Again, our study showed an inverse relationship of both chronic and acute inflammation to cancer, suggesting that the CAM‐cancer association is not driven by CAM being associated with inflammation.…”
Section: Discussionmentioning
confidence: 48%
“…This may have confounded results in previous studies on the relationship between inflammation and cancer. Pathologists do not routinely report the presence and degree of inflammation and atrophy, and those who do, use various grading systems 43,49 . For assessing CAM, the difference between CAM 0 to 1 and CAM 2 to 3 is simple and reproducible in routine practice, that is, <5% vs ≥5% presence.…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic inflammation is common in prostate diseases [7][8][9]25 and it may facilitate cellular proliferation in both benign and malignant conditions. Huang et al 26 reported that mRNA and protein levels of iNOS were significantly increased in the prostate cancer and BPH with histological-prostatitis groups compared to the BPH group, which play important roles in the development and progression of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…p62 is predicted to activate HIF1A, NFκB1, NFKBIA, NFκB (complex), RELA, and SQSTM1(p62) signaling and regulate the activation of IL-1β signaling and the inhibition of NR3C1 function gene set encodes for activation and enrichment of inflammatory pathways like IL-1, IL-8, IL-6, interferon, and TNF receptor signaling. Importantly, inflammatory signaling promotes BCa [9] and PCa [71] progression. We also used IPA to identify cancer-specific networks encoded by the 350 gene set that also include p62 and SOX9 as downstream target signaling molecules and found that IL-1 is predicted to activate molecular programs similar to CTNNB1, Fibroblast Growth Factor (FGF2), and Tumor Necrosis Factor (TNF).…”
Section: Discussionmentioning
confidence: 99%